Examining the associations between weekly training load and match running demands in professional men football players: A descriptive study reflecting contextual variables - da Silva; T. M.; Matos Esteves, P. T.; Clemente, F. M.; Ibáñez Godoy, S. J. (International Journal of Sports Science & Coaching, 2025)
Increasing match running demands require players to receive appropriate stimuli for competitive scenarios. This study characterized the external load of a professional football team during an in-season microcycle and analysed its association with match outcomes (win, draw, loss). A Danish second-division team was monitored during the 2022-2023 season, tracking 25 elite players` external load using GPS across 14 microcycles. Match scores were recorded, and training sessions were categorized based on their proximity to matches. Significant differences were observed in the interaction between training days and match outcomes for total distance covered (F = 6.25, p < 0.001), high sprint running covered (F = 3.29, p = 0.001), number of accelerations (F = 3.57, p = 0.001), number of sprints (F = 2.74, p = 0.006), sprint distance covered (F = 2.85, p = 0.004), maximum speed (F = 5.87, p < 0.001), and dynamic stress load (F = 2.02, p = 0.043). This association was particularly significant on MD-4 for total distance covered, win vs loss (p = 0.031, ES: 1.71) and win vs draw (p < 0.001, ES: 2.38), and MD-3, win vs draw for high-speed running (p < 0.001, ES: 1.49) and sprint distance (p < 0.001, ES: 1.45). A significant decrease in training load across the microcycle was also noted (p < 0.001). This study suggests that intensified training loads at the beginning of the microcycle, followed by tapering appear to be associated with winning matches, whereas lower training loads may be linked to draws and losses.